Tumor Cell Extravasation Mediated by Leukocyte Adhesion is Shear Rate Dependent on IL-8 Signaling - Liang, Shile (2009)
To complete the metastatic journey, cancer cells have to disseminate through the circulation and extravasate to distal organs. However, the extravasation process, by which tumor cells leave a blood vessel and invade the surrounding tissue from the microcirculation, remains poorly understood at the molecular level. In this study, tumor cell adhesion to the endothelium (EC) and subsequent extravasation were investigated under various flow conditions. Results have shown polymorphonuclear neutrophils (PMNs) facilitate melanoma cell adhesion to the EC and subsequent extravasation by a shear-rate dependent mechanism. Melanoma cell-PMN interactions are mediated by the binding between intercellular adhesion molecule-1 (ICAM-1) on melanoma cells and β(2) integrins on PMNs. In addition, the fluid convection affects the extent of activation of β(2) integrins on PMNs by endogenously secreted interleukin 8 (IL-8) within the tumor microenvironment. Results also indicate that shear rate affects the binding kinetics between PMNs and melanoma cells, which may contribute to the shear-rate dependence of melanoma extravasation in a shear flow when mediated by PMNs.